Marketing Strategy Of Fast-Food Restaurants In Indonesia - Sosial Network Analysis On Twitter - Fauline Arizka Putri; Rita Ambarwati; Kumara Adji Kusuma (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – Fast food restaurants are a culinary business where competition is quite tight, especially in the Covid-19 era. To face competition between restaurants which is quite close, companies must have many strategies, one of which is related to the promotion strategy. Aim – This study aims to compare the marketing strategy content between Mcdonald's and Burger King and identify the focus of discussion of Twitter users on fast food restaurants. Design/ Methodology/ Approach – This research uses a social network analysis (SNA) approach with a qualitative descriptive research type. SNA is a form of social computing that extracts large amounts of data. This research uses secondary data sources from tweets with discussions of McDonal's and Burger King in 2017-2022 with data collection. Findings – The study results show that the marketing strategy related to promos carried out by Mcdonald's is Free Shipping, while Burger King's is Cashback. While on the menu, Mcdonald's innovates on the ice cream menu, and Burger King innovates on the burger menu. The marketing strategy related to taste at Mcdonald's and Burger King showed that the two restaurants had a delicious and delicious taste of the products produced by the two companies on the tongues of consumers Conclusion - Burger King's marketing strategy carried out via Twitter social media is superior to McDonlads' marketing strategy. Research implication –The research results show that Burger King is famous for the promos it provides, namely cashback where the promo can be used again when making subsequent purchases by consumers. Apart from that, the menu at Burger King is also very varied, starting from different colors and shapes of burgers, therefore Burger King can attract other consumers to buy their products. This strategy can be maintained to improve and maintain products at Burger King restaurants. McDonald's is famous for its delicious burgers, so this can increase consumer purchases, this strategy must also be maintained. Limitations – This study focuses on two company brands, namely Mcdonald's and Burger King, in this analysis using three marketing strategy criteria as keywords for data collection. The first keyword is a promo, the second is a menu, and the third is taste.